Buoyancy-driven dispersion in a layered porous rock. (12th February 2015) - Farcas, Adrian; Woods, Andrew W.
Abstract: We investigate the longitudinal dispersion of a passive tracer by a gravity-driven flow in a porous medium consisting of a series of independent horizontal layers connected to a constant pressure source. We show that in a formation of given vertical extent, the total flux is only weakly dependent on the number of layers, and is very similar to that in a single layer of the same total depth. However, although the flow speed in each layer is approximately uniform, the speed gradually increases with layer depth. As a result, if a pulse of tracer is released in the flow it will migrate more rapidly through the lower layers, leading to longitudinal dispersion of the tracer. Eventually, the location of the tracer in the different layers may become separated in space so that a sufficiently distant observation well would detect a series of discrete pulses of tracer rather than the original coherent input, as would occur in a single permeable layer. For a constant pressure source, at long times, the standard deviation of the longitudinal distribution of tracer asymptotes to a fraction of order 0.1 of the position of the centre of mass, depending on the number of layers and the overpressure of the source.